Chronicle encyclopedia of history - DK Multimedia (Firm). (New York DK Multimedia, 1997)
Four million years of world history presented through news articles, biographies, themed overviews, video, music, animations, artwork, and pictures. Offers three-dimensional time traveler feature and search and index functions. Includes built-in link to Chronicle Online on the World Wide Web.
System requirements: 486DX/33MHz PC; 12 MB RAM; Windows 95 only; 640 x 480 pixel, 256-color display; 41 MB hard-disk space; double-speed CD-ROM drive; eight-bit sound card; loudspeakers or headphones; mouse.
Keywords: World history